Extraintestinal Amoebiasis: Amebic Liver Abscess in a 48-Year-Old Male Patient - Hans Wincen Winardi (HM Publisher, 2022)
Background: The liver is the most common organ for abscesses. Liver abscesses can be solitary or multiple. Approximately 90% of right-lobe liver abscesses are solitary abscesses, while only 10% of left-lobe abscesses are solitary abscesses. This can occur from hematogenous spread or directly from the site of infection in the peritoneal cavity. Case presentation: A 48-year-old male patient had been administered into the internal medicine ward with the chief complaint of pain in the upper right quadrant of the abdominal increased 3 days before being admitted to the hospital. The patient also complains that pain increase when the patient moves forward and is influenced by activity. The patient walked like a person who carried his stomach. The patient complained of watery stools 3 months ago in ten days, which frequency two to three times a day. The stools are bloody and slimy. Swelling of an upper right quadrant of abdominal since 1 month ago. Decrease of appetite since 1 month ago. Decrease of body weight since 1 month ago, about 5 kilograms. Fever since 2 weeks ago, not high, disappearing, no chill, no sweat. Nauseous since 1 week ago. The patient was admitted to the hospital with awareness of compos mentis, cooperative, and his general condition appeared to be moderately ill, blood pressure 120/80 mmHg, pulse rate 86 times/minute, regular pulse, adequate filling, respiratory rate 24 times/minute, temperature 37ºC. On physical examination, the conjunctiva of the patient’s eyes was anemic. Entamoeba histolytica was found on a routine stool examination. Conclusion: The main clinical manifestations of amoebiasis are right abdominal pain can be features of iron deficiency anemia and reactive thrombocytosis. Diagnosis is based on the finding of characteristic Entamoeba histolytica in the stool. Metronidazole 500 mg three times daily dose resulted in 80% cure and a dose of 750 mg/three times daily for 10 days gave 100% cure. Treatment of reactive thrombocytosis is by curing the basic disease.